Polysaccharides isolated from Bangia fuscopurpurea induce apoptosis and autophagy in human ovarian cancer A2780 cells. Issue 12 (10th October 2021) - Wu, Jingna; Lin, Changhong; Chen, Xiaoting; Pan, Nan; Liu, Zhiyu
Abstract: Although ovarian cancer is common, its prognosis remains poor because of drug resistance and early metastasis. Polysaccharides extracted from Bangia fuscopurpurea (BFP) are potential anti‐cancer agents, but the mechanisms underlying their effects in human ovarian cancer remain unclear. Here, we investigated the mechanisms of action of BFP polysaccharides in A2780 ovarian cancer cells using cell migration, invasion, apoptosis, and autophagy assays. Transwell assays indicated that BFP inhibited cell migration and invasion. Flow cytometry analysis showed that BFP treatment induced apoptosis and reactive oxygen species production, while significantly reducing mitochondrial membrane potential. Reverse transcription–polymerase chain reaction and Western blot analyses revealed changes in the expression of apoptosis‐ and autophagy‐related cellular mRNAs and proteins, respectively, following BFP treatment for 24 h. Transmission electron microscopy revealed that BFP induced autophagy in A2780 cells. These findings demonstrate that BFP may be useful for developing functional foods for cancer therapy. Abstract : BFP suppresses human ovarian cancer A2780 cell migration, and invasion. BFP induces mitochondria‐mediated apoptosis and autophagy in A2780 cells. BFP may possess anti‐ovarian cancer properties in vitro.